Modern scientific research on semantic field theory - Ismoilova Dilorom, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Irrefutably, many scientific works are conducted following the principles of structural linguistics. In linguistics, the study of linguistic units by dividing them into different meaningful groups on a thematic basis provides new scientific conclusions to the science. A systematic approach to the area under study during scientific research provides sheer opportunity for the researcher to study in groups and identify similarities and differences of units belonging to the semantic group or field. Field theory is used to investigate the language listem dividing into many microsystems. The article discusses modern research which contributed to the development of the field theory. The author highlights essential theories presented by researchers and analysed their scientific conclusions concerning practical results.